PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS ATTENTION, RELEVANCE, CONFIDENCE, AND SATISFACTION (ARCS) PADA SUBTEMA 1 SUMBER ENERGI UNTUK SISWA KELAS III SEKOLAH DASAR - Cahyo Dwi Andita; Andri Valen (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop teaching materials in the form of LKPD based on attention, relevance, confidence, and satisfaction (arcs) on subtheme 1 of energy sources for grade III elementary school students that are valid, practical and effective. This type of research is Research and Development with the ADDIE development model. Data collection techniques through interviews, questionnaires, tests, and documentation with research subjects being grade III students of SD 2 Raksa Budi. Based on the results of the analysis of the validation test of LKPD based on attention, relevance, confidence, and satisfaction (arcs) on subtheme 1 of energy sources for grade III elementary school students assessed by three experts, namely, language experts, media experts, and material experts, it meets the validity criteria with an average score of 0.87. Meanwhile, from the results of the analysis of the assessment of the practicality sheets of teachers and students, it was obtained that the LKPD attention, relevance, confidence, and satisfaction (arcs) on subtheme 1 of energy sources for grade III school students met the practical criteria with an average score of 92.8%. Then the analysis of the effectiveness assessment obtained an average N-Gain score of 0.70 with an effective category. Based on the results of the study, it can be concluded that the LKPD based on ARCS on subtheme 1 of energy sources for grade III students of schools is valid, practical, and effective so that it is suitable for use in the learning process in grade III of SD 2 Raksa Budi